Forcing substitution of tantalum by copper in 1T-TaS2: synthesis, structure and electronic properties of 1T-CuxTa1−xS2. (28th August 2018) - Sachs, Malte; Bohnen, Kirsten; Conrad, Matthias; Klein, Benedikt P; Krug, Claudio K; Pietzonka, Clemens; Schmid, Martin; Zörb, Steffen; Gottfried, J Michael; Harbrecht, Bernd
Abstract: We investigated the compound 1T-Cu x Ta1− x S2 with respect to its synthesis, homogeneity range, structure and electronic properties. The average structure of 1T-Cu x Ta1− x S2 resembles that of the high-temperature phase of the layered transition metal dichalcogenide 1T-TaS2 in which tantalum is partially substituted by copper. 1T-Cu x Ta1− x S2 readily decomposes at elevated temperatures and can only be prepared and stabilized by a sufficiently high amount of sulfur excess. XPS and NEXAFS measurements reveal that copper has the oxidation state +I in 1T-Cu x Ta1− x S2, which is supported by quantum chemical calculations. The disorder introduced by copper doping causes an Anderson-type localization of the conduction electrons as manifested by a strong increase of the electrical resistivity and a Curie-type paramagnetism at low temperatures as in other doped systems 1T- M x Ta1− x S2 with higher valent metals. Quantum chemical calculations support this interpretation.